FACTORS THAT INFLUENCE AUDIT LAG IN NON-CYCLICAL CONSUMER SECTOR COMPANIES - Tandi, Jordy; Daryatno, Andreas Bambang (International Journal of Application on Economics and Business, 2023)
The purpose of this study was to examine the effects of comprehensive income, total assets, and KAP size on audit lag. Audit lag is the time span for completing the audit of annual financial statements, namely from the closing date of the company's books to the date stated in the independent auditor's report, the sample selection method for this study is purposive sampling, which is a sampling method based on certain criteria set by the researcher. The research method used in this research is multiple analysis regression. The samples used in this study were 30 companies engaged in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the 2020-2022 period, the data used was secondary data. The results of this study are as follows: total assets, KAP size, and comprehensive income have an effect on audit lag.